Relative bioavailability of an extemporaneously prepared aprepitant oral suspension in healthy adults. (December 2019) - Patel, Priya; Nathan, Paul C; Walker, Scott E; Zupanec, Sue; Volpe, Jocelyne; Dupuis, L Lee
Purpose: Use of aprepitant for chemotherapy-induced nausea and vomiting prophylaxis in patients unable to swallow capsules is hindered by the lack of a commercially available oral liquid formulation in many jurisdictions. A stable oral suspension can be extemporaneously prepared using commercially available capsules. We aimed to determine the bioavailability of this aprepitant suspension relative to the capsule. Methods: This two-period crossover study enrolled 17 healthy adult volunteers. Volunteers received a single 125 mg aprepitant dose during each study period. Order of formulation presentation (capsule vs suspension first) was randomized. Thirteen blood samples were collected over a 48-h period. Aprepitant plasma concentrations were determined using liquid chromatography-mass spectroscopy. Relative bioavailability was defined as the geometric least squares mean ratio for area under the concentration versus time curve (AUC) from time zero to infinity of the aprepitant suspension versus the capsule. Bioequivalence, defined as per Health Canada guidelines, was assessed as a secondary aim. Results: Relative bioavailability of the aprepitant suspension was 82.3% (90% CI: 69.09-98.00%). Bioequivalence was not established: geometric least squares mean ratios (suspension/capsule) for AUC time zero to 48 h and maximum concentration were 87.8% (90% CI: 75.48–102.16%) and 86.1% (90% CI: 75.59–98.16%), respectively. No serious adverse events were observed. Conclusions: With a relative bioavailability of 82.3%, the extemporaneous aprepitant oral suspension was well-absorbed relative to the capsule. Though not bioequivalent to the oral capsule, the clinical use of this aprepitant oral suspension in adult and pediatric patients unable to swallow capsules is likely to be effective and safe.